2002
DOI: 10.1046/j.1365-2222.2002.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotrienes induce human eosinophil locomotion and adhesion molecule expression via a CysLT1 receptor‐mediated mechanism

Abstract: These data demonstrate that CysLTs are active in vitro in directly up-regulating human eosinophil functions involved in eosinophil recruitment. The down-regulation of Mac-1 expression and eosinophil chemotaxis by the potent and selective CysLT1 receptor antagonist montelukast indicated the specificity of the LTC4-, LTD4- and LTE4-induced response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 33 publications
4
67
1
Order By: Relevance
“…In a recent study, the CysLT 1 R has been associated with cytokine transduction signals for the up-regulation of eosinophilopoiesis by IL-13 and eotaxin in murine bone marrow (Queto et al, 2010). These data support early reports demonstrating the inhibitory action of CysLT 1 R antagonists on eosinophil activation and migration (Virchow et al, 2001;Fregonese et al, 2002;Suzuki et al, 2003;Ueda et al, 2003;Saito et al, 2004;Nagata et al, 2005), as well as on adhesion (Fregonese et al, 2002;Nagata et al, 2002;Kushiya et al, 2006;Meliton et al, 2007;Profita et al, 2008). There is considerable information available to demonstrate the ability of CysLTR antagonists to reduce airway eosinophilia and eosinophil cationic protein (ECP) in animals (Underwood et al, 1996;Ihaku et al, 1999) and in humans (Pizzichini et al, 1999;Obase et al, 2002;Steinke et al, 2003;Strauch et al, 2003;Laitinen et al, 2005;Kopriva et al, 2006).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 74%
“…In a recent study, the CysLT 1 R has been associated with cytokine transduction signals for the up-regulation of eosinophilopoiesis by IL-13 and eotaxin in murine bone marrow (Queto et al, 2010). These data support early reports demonstrating the inhibitory action of CysLT 1 R antagonists on eosinophil activation and migration (Virchow et al, 2001;Fregonese et al, 2002;Suzuki et al, 2003;Ueda et al, 2003;Saito et al, 2004;Nagata et al, 2005), as well as on adhesion (Fregonese et al, 2002;Nagata et al, 2002;Kushiya et al, 2006;Meliton et al, 2007;Profita et al, 2008). There is considerable information available to demonstrate the ability of CysLTR antagonists to reduce airway eosinophilia and eosinophil cationic protein (ECP) in animals (Underwood et al, 1996;Ihaku et al, 1999) and in humans (Pizzichini et al, 1999;Obase et al, 2002;Steinke et al, 2003;Strauch et al, 2003;Laitinen et al, 2005;Kopriva et al, 2006).…”
Section: Receptor Expression Patterns With Functional Significancesupporting
confidence: 74%
“…Blockade of leukocyte chemotaxis has been reported to alleviate EAE (31,32). It has been reported that CysLTs induce chemotactic activity in eosinophils (33) and monocytes (34). We wondered whether CysLTs also induce the chemotaxis of pathogenic T cells in EAE.…”
Section: Montelukast Blocks Ltd 4 -Induced Leukocyte Chemotaxismentioning
confidence: 96%
“…9 They are also believed to play an important role in cell trafficking and innate immune responses. CysLTs are potent chemoattractants for eosinophils 10 and CD34 + hematopoetic progenitor cells. 11 CysLTs also promote migration of monocyte-derived dendritic cells in response to CCL19.…”
Section: Introductionmentioning
confidence: 99%